2007
DOI: 10.1007/s11136-007-9187-3
|View full text |Cite
|
Sign up to set email alerts
|

Parent-proxy and child self-reported health-related quality of life: using qualitative methods to explain the discordance

Abstract: This study provides evidence to suggest that discordance among parent-child pairs on KIDSCREEN scores may be as a result of different reasoning and different response styles, rather than interpretation of items. These findings have important implications when parent-proxy reported HRQOL is used to guide clinical/treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
167
1
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(204 citation statements)
references
References 35 publications
13
167
1
23
Order By: Relevance
“…Consistently lower proxy-than selfreports may indicate that parents' ratings could be influenced by their concerns and worries or by experienced burdens (e.g., burdens that are due to concurrently having to work and care for their family), or by their own health conditions. Furthermore, it is possible that this general pattern occurs because (1) children tend to provide more extreme answers than their parents; and/or (2) children and parents differ with respect to the reasons they provide for their answers [35]-a pattern that possibly occurs independent of the health status of the child. The higher selfversus proxy ratings also were confirmed by the method of Sattoe et al [13] and were in line with this particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently lower proxy-than selfreports may indicate that parents' ratings could be influenced by their concerns and worries or by experienced burdens (e.g., burdens that are due to concurrently having to work and care for their family), or by their own health conditions. Furthermore, it is possible that this general pattern occurs because (1) children tend to provide more extreme answers than their parents; and/or (2) children and parents differ with respect to the reasons they provide for their answers [35]-a pattern that possibly occurs independent of the health status of the child. The higher selfversus proxy ratings also were confirmed by the method of Sattoe et al [13] and were in line with this particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we conducted a qualitative study using a think-aloud methodology with parents and children (8-12y) completing KIDSCREEN. 2 The results demonstrated that there was discordance between parents and DOI: 10.1111/j.1469-8749.2008.0 016 x . 7…”
mentioning
confidence: 94%
“…söz konusudur (17,18) . Özellikle yaş ve ağır hastalık durumlarında çocuk hakkında daha etkili bilgi alabilmenin önemli bir yolu vekil-ebeveyn değerlendirmesidir (18) .…”
Section: Introductionunclassified
“…Özellikle sorgulanan kavramlar benzer şekilde algılansa bile verilen yanıtların birbiriyle uyumsuz olabileceği, çünkü çocuğun çevresiyle bir bütün olarak gerçekliği algılayışı ile ebeveynin algı-layışı arasındaki farklılığın elde edilen bu uyumsuzlukta belirleyici olduğu belirtilmektedir (17,19) . Bu amaçla geliştirilen ölçeklerin güvenilirliğinin bir gös-tergesi de vekil ile öz bildirim sürümlerindeki tutarlı-lıktır (18) .…”
Section: Introductionunclassified